Understanding the Factors Behind Tantrum Behavior in Early Childhood: A Study from Barru District - Haniarti Haniarti; Nur Afni; Rini Anggraeny (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2024)
Tantrums are intense anger outbursts that occur when children struggle to communicate their needs and goals. They are common in children who are highly energetic, ambitious, and active. Inconsistent parenting and unrealistic expectations often make the problem worse. These factors can lead to challenges in emotional regulation, particularly in children aged 18 months to 4 years. This study aimed to explore the causes of tantrum behavior in early childhood in Barru District, Barru Regency. Using a quantitative cross-sectional design, researchers gathered data from 90 eligible respondents. The study used interviews, observations, and Likert-scale questionnaires to collect information. Data analysis was conducted with the chi-square test at a significance level of α = 0.05. The results revealed significant links between tantrum behavior and several factors. Physiological issues, psychological challenges, environmental influences, and parenting practices all showed strong associations (p = 0.000 for each factor). These findings emphasize the interconnected nature of these elements in shaping tantrum behavior. In conclusion, this study proves that tantrum behavior in early childhood is not caused by a single factor. Instead, it results from a combination of psychological, environmental, and parenting factors. Understanding these relationships can help parents and caregivers better address emotional challenges in young children.